High-performance quasi-vertical GaN Schottky barrier diode with anode selective fluorine treatment. (10th October 2019) - Chen, Jiabo; Bian, Zhaoke; Liu, Zhihong; Ning, Jing; Duan, Xiaoling; Zhao, Shenglei; Wang, Haiyong; Tang, Qing; Wu, Yinhe; Song, Yuqin; Zhang, Jincheng; Hao, Yue
Abstract: In this letter, we report a high performance GaN quasi-vertical Schottky barrier diode (SBD) on sapphire substrate with a planar anode selective fluorine treatment (SFT). The presented SBD with anode SFT–SBD exhibits a large forward current density over 2 kA cm −2 and a low differential specific on-resistance of 0.49 mΩ cm 2 . Compared to the conventional SBD, the leakage current of SFT–SBD is suppressed over 4 orders of magnitude, leading to the breakdown voltage (BV) dramatically improved from 78 to 145 V, but without severe degradation of the on-state performance. The simulation results indicate that the anode SFT can effectively reduce the path of leakage current at reverse bias, leading to the suppressed leakage current thus enhanced BV.